Effect of methyl methacrylate grafted natural rubber-49 on mechanical properties of filled calcium carbonate unplasticised PVC - Lim, J. W.; Hassan, Azman; Abu Bakar, Aznizam (2002)
Unmodified unplasticised PVC (PVC-U) has the disadvantages of being prone to occasional brittleness and is notch sensitive. Various types of rubber are being used in PVC-U as impact modifier which formed multi-phase systems. The main objective of this research is to study on possibility of methyl-methacrylate-grafted-natural rubber-49 (MF49) to be used as impact modifier in filled calcium carbonate unplasticised PVC. MG 49 is a modified NR which is made by polymerizing methyl methacrylate monomer in latex so that polymer chains become attached to the rubber molecule. In the sample preparation, dry blending was carried out with laboratory blender and milled into sheets using two-roll mill. Test specimens were molded using a hot press before carrying out the various mechanical testing that is impact, flexural and tensile testing. The results show that rhe impact strenght increases as the impact modifier MG 49 contect increases in the filled calcium carbonate PVC-U samples. However, similar increase in the impact modifier content resulted in a decrease in flexural modulus and yield stress. The formulation containing 8 phr impact modifier MG 49 and 10 phr calcium carbonate was found to be most optimum formulation in term of impact strength, flexural modulus and yield strength.